Implementasi Six Sigma untuk Perbaikan Produk Nickel Pig Iron - Jihan Shofa, Mohamad; Gunawan, Hadi (Universitas Serang Raya, 2017)
PT. INF is a steel mining company. It produce such as nickel pig iron. Nickel pig iron used raw materials stainless steel factory, nickel and steel mill rolls. The number of defective products for nickel pig iron in a few months getting on upward trend. This research will analyze the cause of the increasing defect product by using Six Sigma methode. Furthermore, the proposed improvement is done by using the failure mode and effect analysis (FMEA) approach. The results shows the main problems are the higher value of Silica (Si) and phospor (P), the sigma level is obtained from the annual pig iron making process in 1.6 sigma, process improvement need to be done are monitoring and scheduling of burnlime powder orders, checking new materials by testing the formula against new materials, and making a repair schedule as well as focusing on changes in pressure on the monitor screen